2020
DOI: 10.1016/j.neuropharm.2020.108251
|View full text |Cite
|
Sign up to set email alerts
|

Clinical potential of a rationally engineered enzyme for treatment of cocaine dependence: Long-lasting blocking of the psychostimulant, discriminative stimulus, and reinforcing effects of cocaine

Abstract: It is a grand challenge to develop a truly effective treatment of substance use disorder (SUD), particularly for cocaine and other drugs without an FDA-approved treatment available, because a truly effective therapy must effectively block the drug's physiological and reinforcing effects during the entire period of treatment in order to achieve the long-time abstinence required by the FDA. Whether a biologic, such as monoclonal antibody, vaccine, or therapeutic enzyme, can be truly effective for SUD treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…It has been demonstrated that these proteins are capable of accelerating cocaine metabolism, rapidly detoxifying cocaine and its toxic metabolites 22,27–30 . A single dose of the CocH‐Fc can effectively block the physiological and reinforcing effects of cocaine for a long period of time (weeks) 25,27,31 . Specially, we have also demonstrated that CocH‐Fc can also block cocaine‐induced DAT trafficking in cocaine‐naïve rats 11 .…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…It has been demonstrated that these proteins are capable of accelerating cocaine metabolism, rapidly detoxifying cocaine and its toxic metabolites 22,27–30 . A single dose of the CocH‐Fc can effectively block the physiological and reinforcing effects of cocaine for a long period of time (weeks) 25,27,31 . Specially, we have also demonstrated that CocH‐Fc can also block cocaine‐induced DAT trafficking in cocaine‐naïve rats 11 .…”
Section: Introductionmentioning
confidence: 51%
“…Furthermore, Fc‐fused CocHs can block cocaine‐induced hyperactivity, cocaine discrimination and cocaine self‐administration (associated with i.v. infusion of cocaine) 31 . In particular, CocH3‐Fc(M3) was proved capable of effectively limiting the brain cocaine concentration and preventing cocaine‐induced hyperactivity and DAT trafficking to plasma membrane from acute cocaine exposure 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The locomotor data are plotted as the mean ± SEM metres travelled in 5-min bin during locomotor activity for 7 h. Particularly for the lethal dose (60 mg/kg), in addition to the hyperactivity, 60-mg/kg cocaine induced convulsion in six out of eight rats, with two rats died after convulsion, 37 Particularly for treatment of cocaine abuse, previous studies 20,23,30,37,41,43 demonstrated that an exogenous CocH (known as a BChE mutant with at least 1000-fold improved catalytic efficiency against cocaine compared to wild-type BChE) can powerfully rescue rats by rapidly detoxifying cocaine and its toxic metabolites 25,27,29,44 at any time point as long as rats are still alive, and also effectively block cocaine-induced hyperactivity. 23,28,30,37,45 However, it was unknown whether an enzyme can also effectively block cocaine-induced DAT trafficking to plasma membrane. According to the animal data with CocH3-Fc(M3) treatment, the enzyme is capable of effectively preventing cocaine from reaching the brain and limiting the brain cocaine concentration to be lower than the threshold (2.0 ± 0.8 μg/g) even with a lethal dose of 60-mg/kg cocaine (ip).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for treatment of cocaine abuse, previous studies 20,23,30,37,41,43 demonstrated that an exogenous CocH (known as a BChE mutant with at least 1000‐fold improved catalytic efficiency against cocaine compared to wild‐type BChE) can powerfully rescue rats by rapidly detoxifying cocaine and its toxic metabolites 25,27,29,44 at any time point as long as rats are still alive, and also effectively block cocaine‐induced hyperactivity 23,28,30,37,45 . However, it was unknown whether an enzyme can also effectively block cocaine‐induced DAT trafficking to plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation